Allocation of Investment in Work and Family Roles: Alternative Theories and Implications for Research - Lobel, Sharon A. (Academy of Management Review, 1991)
The process of people's investment in work and family roles is poorly understood. Traditionally, investment in such roles has been considered the product of utilitarian motives. An alternative perspective, derived from social identity theory, suggests that identity salience determines this investment. Proponents of the two approaches differ in describing sources of work-family conflict and methods of achieving work-family balance. Despite the competing predictions of the two approaches future research on the moderating effects of gender, life stage, and culture may prove fruitful for researchers who wish to elaborate upon an integrated model.